2020
DOI: 10.5194/bg-17-5285-2020
|View full text |Cite
|
Sign up to set email alerts
|

Global peatland area and carbon dynamics from the Last Glacial Maximum to the present – a process-based model investigation

Abstract: Abstract. Peatlands are an essential part of the terrestrial carbon cycle and the climate system. Understanding their history is key to understanding future and past land–atmosphere carbon fluxes. We performed transient simulations over the last 22 000 years with a dynamic global peat and vegetation model forced by Earth system model climate output, thereby complementing data-based reconstructions for peatlands. Our novel results demonstrate a highly dynamic evolution with concomitant gains and losses of activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 116 publications
(223 reference statements)
3
22
0
Order By: Relevance
“…The spread between simulations forced with climate anomalies from the different CMIP6 climate models indicates a large climate anomaly related uncertainty in simulated peatland variables. This is in line with previous studies that also found a large uncertainty propagation from climate variables to peatland and carbon cycle variables in general (Stocker et al, 2013;Ahlström et al, 2017;Qiu et al, 2020;Müller and Joos, 2020).…”
Section: Climate Forcing Uncertaintysupporting
confidence: 93%
See 4 more Smart Citations
“…The spread between simulations forced with climate anomalies from the different CMIP6 climate models indicates a large climate anomaly related uncertainty in simulated peatland variables. This is in line with previous studies that also found a large uncertainty propagation from climate variables to peatland and carbon cycle variables in general (Stocker et al, 2013;Ahlström et al, 2017;Qiu et al, 2020;Müller and Joos, 2020).…”
Section: Climate Forcing Uncertaintysupporting
confidence: 93%
“…The dynamic global vegetation model LPX-Bern was used to estimate committed and projected mid to long term future changes of global peatland area and carbon under three different climate and land-use scenarios. A previously published transient simulation from the Last Glacial Maximum to the present (Müller and Joos, 2020) was used as the starting point for the future projections, accounting for the transient history and potential legacy effects of today's and former peatlands. LPX-Bern was forced by climate anomalies from ten different CIMIP6 earth system models, selected to optimally represent the full CIMIP6 ensemble range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations